Análise fonético-acústica do contraste fônico de vozeamento em crianças - Gregio, Fabiana Nogueira (2013)
Objective: to investigate implementation strategies for phonic voicing contrast in Brazilian Portuguese in a study group of children with speech alteration in comparison to a control group of children without alteration. Methods: we selected six subjects ranging from 7-10 years old, three with diagnosis of alterations in the production of voicing contrast in speech and three as controls. Six carrier sentences with target disyllabic words in a CVCV structure, containing voice and voiceless pairs of plosive consonants in Brazilian Portuguese in contexts of tonic and post-tonic syllables, were audio recorded (five random repetitions). The collected samples were acoustically investigated, labeled and submitted to procedures to extract caustic measures of fundamental frequency (f0) in the beginning and in the stationary point of the vowel following the plosive consonant, frequency of first formant (F1) in the beginning and in the stationary point of the vowel following the plosive consonant and duration measures of: plosive consonant, vowel preceding the the plosive consonant, vowel following the plosive consonant, voice-onset-time (VOT) in the plosive consonant, voicing period, voiceless period, voicing redemption, total pre-plosion and plosion times. We also measured the VCV excerpt of the target word to calculate relative duration. Speech samples were then submitted to a perception experiment for auditive judgment (vocable identification) by a group of 35 judges. Acoustic measure results were submitted to sample comparison test, hierarchical cluster analysis and discriminate analysis. Tasks in the auditive judgment were presented by means of confusion matrices and calculation of auditive distances. Correspondence data between acoustic and perceptive findings were submitted to logistics regression analysis. The research project was approved by the Research Ethics Committee (119/09). Results: acoustic measures were compared between voiceless and voiced plosive consonant pairs and, in general, showed significant differences. However, voiceless and voiced plosive consonants were grouped differently in the different contexts in each group studied and also showed predictive capacity to identify control and study groups. With regard to perception, auditive distances showed to be smaller for the study group samples in comparison to the control group in the tonic context. In the post-tonic context, auditive differences were similar between the two groups. Consonant duration, from voiceless and total pre-plosion periods (tonic context) and total pre-plosion duration and voicing period (post-tonic context) showed predictive power in the auditive judgment of voicing contrast in speech alterations of voiced plosive consonants. For voiceless plosive consonants, influent measures included f0 in the beginning of the vowel and duration of previous vowel (tonic context) and f0 in the beginning of the vowel and duration of plosive consonant (post-tonic context). Conclusion: investigation of implementations found in children s speech signal showed that duration measures were influent in identifying speech with voicing contrast alterations, signaling traces of implementation of more than one action to analyze voicing contrast